Satisfaction of Sport Participants Used of City Park - Pudia M Indika; Siti Fatimah (Science and Environmental Journal for Postgraduate, 2020)
City parks is part of public Open Green Space (OGS) for social and aesthetic interactions including sports activities. The scope of sports that utilize city parks are educational sports, recreational sports and achievement sports. Imam Bonjol city park is one of the green space used for activities due to the availability of sports facilities. Community visits to exercise fluctuate, most on holiday. Aim the study is to determine the level of perception of sport satisfaction in the Imam Bonjol city park. Type of research is descriptive study. The research sample of 40 people with incidental sampling techniques. The research instrument used a Likert scale questionnaire about comfort, positive attitude and the utilization of the advantages of city parks. The results showed the level of perception of sports satisfaction in the city park Imam Bonjol in the good category with a percentage value of 72.46%. Interaction between participants and the physical environment, social environment in city parks in carrying out sports activities for the sustainability of public health.